KEJADIAN HIPERTENSI PADA PASIEN DI PUSKESMAS HARAPAN RAYA KOTA PEKANBARU - Renny Fitriana (Jurnal Kesehatan Husada Gemilang, 2018)
Hypertension is one of the number one killer diseases in the world today. Age is one of the risk factors of hypertension. The normal value of a person’s blood pressure with a height, a weight, normal activity level and health in general is 120/80 mmHg. This study is to diagnose the factors associated with the incidence of hypertension in patients. This research is quantitative observational analysis with cross sectional design. Data analysis was completed thru univariate and bivariate using Chi-square test. The population of research were adult patient who visited Harapan Raya Health center. The sample was 91 people. The result shows the value for the incidence of hypertension on gender variables (p-value= 0,008), heredity (p-value= 0,013) and physical activity (p-value= 0,000), while obesity variable doesn’t show significant relationship (p-value= 0,249). It can consequently be concluded that the incidence of hypertension can be prevented if diligent to check blood pressure regularly.